Review, Analyses of azo dyes' synthesis, characterization and biological activity (Texas Journal of Multidisciplinary Studies, 2022)
In this review essay, we discuss how dyes are used to color materials, particularly clothes. These dyes are colored by chromospheres, which are functional groups that absorb light. Azolo, nitro, and carbonyl groups are the most prevalent chromospheres. Another crucial component of dyes is auxochromes, which are functional groups that intensify color. Hydroxyl, amino, sulfate, and carboxylate groups are the most typical chromospheres. Nitrogen to nitrogen double bond serves as the chromosphere in azo dyes. Diazonium salt is combined with a highly active aromatic system to produce these colors.